Channa andrao, a new species of dwarf snakehead from West Bengal, India (Teleostei: Channidae) - Britz, Ralf (Zootaxa, 2013)
Channa andrao, new species, from Lefraguri swamp, West Bengal, India, differs from all its congeners except, C. asiatica, C. bleheri and C. burmanica and the recently described C. hoaluensis and C. ninhbinhensis by the absence of pelvic fins. It can be distinguished from all other pelvic fin-less species of snakeheads by its colour pattern, and differs further in its number of vertebrae, dorsal- and anal-fin rays, and lateral-line scales from individual snakehead species in this complex. Channa andrao raises the number of snakehead species endemic to the Eastern Himalaya biodiversity hotspot to ten, representing almost one third of the known species in the genus.